Earnings-Based Compensation Plans, Performance, and Capital Expenditure Policy in the Motor Carrier Industry. - Enis, Charles R. (The Accounting Review, 1993)
This research examines the effect that adoption of earnings-based incentive plans has on performance and capital expenditure policy in the motor carrier industry. The motor carrier industry provides the opportunity to study the effect of incentive plans on small, closely-held organizations. Restricting the sample to a single industry controls for variations in accounting procedures, heterogeneous production functions, and other environmental factors. Firms that adopted bonus and performance plans are matched with similar firms without such plans. The matching criteria are size, carrier type, and freight classification. The dependent variables are operating ratio, net income, capital expenditures, and maintenance expenditures. The analysis investigates the extent to which the groups differ in performance and investment policy before and after plan adoption. The results indicate that motor carriers that adopted bonus plans had out-performed the respective control firms during the post-adoptive period. This relatively improved performance is not linked to reductions in capital or maintenance expenditures. Although the results for performance plan adopters are in the expected directions, they are not statistically significant.